Otimização da extração de compostos bioativos do bagaço de oliva por diferentes métodos de extração - Batista, Vanessa Sabrina Fagundes (2023)
Given the extensive cultivation of olive trees to obtain olive oil and the amount of pomace generated during this processing, it is interesting to utilize this by-product, mainly because many bioactive compounds remain in the pomace after olive oil production. It makes this by-product rich in nutrients with economic and environmental characteristics at industrial levels. Due to the few studies in the literature on the recovery of bioactive compounds from the olive pomace, this study aimed to optimize the bioactive compounds extraction from olive pomace using different methods with green technologies for faster extraction and reduction of toxic waste. The extracts were obtained by method Microwave Hydro-diffusion and Gravity (MHG), applying a central composite rotational design (CCRD), with two independent variables (22), with different power (X1) (40, 100, 250, 400 and 462 Watts) and time (X2) (10, 15, 20, 22 minutes), containing three central and four axial points, resulting in 11 experiments. And obtained by conventional extraction method and ultrasound, following the statistical model Tukey tested different concentrations of ethanol solvent (0, 15, 50, 85, and 100%) at different temperatures (20, 26, 40, 55, and 60 ºC). The MHG extraction method suggests using 100W of power to obtain a higher concentration of phenolic compounds in olive pomace. There were no significant differences in the extraction of flavonoids and antioxidant capacity of the olive pomace extracts in the other potencies (W) and times (min) analyzed. And time for the results obtained by conventional extraction and ultrasound, it showed that the samples extracted by the ultrasound method usin diferente concentrations of etanol at a temperature of 40ºC, presented the best results for the antioxidante activity (ORAC) of the olive pomace extracts, showing no difference significant forphenolic compounds and flavonoids.